Blueberry Attenuates Liver Fibrosis, Protects Intestinal Epithelial Barrier, and Maintains Gut Microbiota Homeostasis - Zhiqiang Yan; Fang Yang; Zhu Hong; Shishun Wang; Zhang Jinjuan; Bing Han; Rujia Xie; Feiyun Leng; Qin Yang (Canadian Journal of Gastroenterology and Hepatology, 2019)
Objective. Recently, blueberry has been identified as a candidate for the treatment of liver fibrosis. Given the role of gut-liver axis in liver fibrosis and the importance of the gut microbiota homeostasis to the maintenance of the intestinal epithelial barrier, this study aimed to investigate whether blueberry could attenuate liver fibrosis and protect the intestinal epithelial barrier by maintaining the homeostasis of the gut microbiota. Method. A CCl4-induced rat liver fibrosis model was used to detect the roles of blueberry in liver fibrosis and intestinal epithelial barrier. The liver weight and body weight were measured, the liver function was monitored by ALT and AST activity, protein and mRNA were determined by western blot and RT-qPCR, and the gut microbiome was detected by Miseq. Results. The results showed that blueberry could reduce the rate of liver weight/body weight gain (p<0.05), ALT (p<0.01) and AST (p<0.05) activity, and the expression of collagen I (p<0.01), collagen IV (p<0.01), and α-SMA (p<0.01) expression in CCl4-induced rat liver. CCl4 impaired the intestinal epithelial barrier and decreased the expression of the tight junction protein. Blueberry restored the intestinal epithelial barrier and increased the expression of the tight junction protein. The gut microbiota homeostasis was impaired by CCl4, but after treatment with blueberry, the intestinal flora returned to normal. Conclusion. Blueberry attenuated liver fibrosis, protected intestinal epithelial barrier, and maintained the homeostasis of the gut microbiota in a CCl4-induced injury rat model.